Pola Legitimasi “Criminal-Policy” Pada Pembentukan Peraturan Daerah - Sri Wahyu Kridasakti; Purwaningdyah Purwaningdyah; Eko Nuriyatman (Recital Review, 2023)
In the absence of standards regarding the establishment of existing regional regulations in Indonesia related to public order by local governments which contain criminal sanctions, this creates deviations in terms of the principles of legal certainty for the community. This scientific article discusses the formation of criminal policies by regional governments that have the same cultural similarities and have the same basis for legitimacy. The research approach used is socio-legal, the related issue is regarding the study of criminal-policy legal issues and the locus of government of the Special Region of Yogyakarta. With the same cultural group, namely Mataraman in the formation of criminal policies. Based on the results of the research, it was found that the formation of the Tibum Regional Regulation in Yogyakarta shows the use of different legitimacy bases in the formation of its criminal policy. Differences in the determination of criminal sanctions for the object of the same regulation, for selling in prohibited areas, environmental pollution, erection of illegal buildings and others, the threat of administrative fines and imprisonment varies, with fines ranging from IDR 50,000,000 to imprisonment for around 6 month. The acceptance in complexiu of the living-law values ​​with their local wisdom in the formation of regional regulations in the field of public order was apparently nowhere to be found, so that the basis for the legitimacy of criminal-policy norms was built only on technocratic uptake. Abstrak Dengan tidak adanya standar mengenai pembentukan peraturan daerah yang ada di Indonesia terkait dengan tertib umum oleh pemerintah daerah yang bermuatan sanksi pidana, menimbulkan penyimpangan dalam hal asas-asa kepastian hukum bagi masyarakat. Artikel ilmiah ini membahas mengenai pembentukan criminal policy oleh pemerintahan daerah yang memiliki keserupaan kultur budaya yang sama memiliki dasar ukuran legitimasi yang sama. Pendekatan penelitian yang digunakan adalah socio-legal, isu terkai adalah mengenai kajian isu hukum criminal-policy dan lokus pemeritahan Daerah Istimewa Yogyakarta. Dengan keserumpunan  budaya yang sama yaitu Mataraman dalam pembentukan criminal-policy.  Berdasarkan kepada hasil penelitian didapat data bahwa pembentukan Peraturan Daerah Tibum di Yogyakarta menunjukkan penggunaan dasar legitimasi berbeda-beda dalam pembentukan criminal policy-nya. Perbedaan penetapan sanksi pidana pada obyek pengaturan yang sama, terhadap berjualan pada area terlarang, pencemaran lingkungan, pendirian bangunan liar dan lain-lainnya, ancaman denda administrasi maupun pidana kurungannya ternyata berbeda-beda dengan denda berkisar Rp50.000.000,- dengan pidana kurungan sekitar 6 bulan. Receptio in complexiu atas nilai-nilai the living-law dengan local wisdom-nya dalam pembentukan peraturan daerah bidang ketertiban umum ternyata tidak ada ditemukan, sehingga dasar legitimasi norma criminal-policy dibangun berdasarkan serapan teknokratis saja.